2012
DOI: 10.1210/jc.2012-1845
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Sleep Restriction and Recovery on Metabolic Outcomes

Abstract: Sleep often seems undervalued in modern society, but this may have widespread metabolic consequences as described in this review. Acute sleep loss is often unavoidable, but chronic sleep restriction ideally should not be. Understanding the implications of both sleep restriction and recovery on metabolic outcomes will guide public health policy and allow clinical recommendations to be prescribed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 113 publications
3
67
0
5
Order By: Relevance
“…Based on our present data, the daily light exposure may thus well explain the circannual cycle of BAT detectability. Similarly, impaired BAT activity may also explain, at least partly, the relationship between obesity and disturbances in circadian rhythmicity in humans by light pollution (2,3,34), and possibly also by shift work (35)(36)(37) and sleep curtailment (1,38,39). Additionally, our data may provide the link in the relationship between exposure to light in the bedroom and obesity (4).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Based on our present data, the daily light exposure may thus well explain the circannual cycle of BAT detectability. Similarly, impaired BAT activity may also explain, at least partly, the relationship between obesity and disturbances in circadian rhythmicity in humans by light pollution (2,3,34), and possibly also by shift work (35)(36)(37) and sleep curtailment (1,38,39). Additionally, our data may provide the link in the relationship between exposure to light in the bedroom and obesity (4).…”
Section: Discussionmentioning
confidence: 69%
“…M odern world society is subjected to disturbances of circadian rhythms by shift work, sleep deprivation, and environmental light pollution. Importantly, the increasing prevalence of obesity is associated with a disrupted sleep-wake pattern in humans (1) and coincides with the availability of artificial light (2,3). Additionally, a recent study revealed a relationship between exposure to light at night and obesity in a cross-sectional analysis of over 100,000 women (4).…”
mentioning
confidence: 99%
“…At baseline, actigraphy showed that on average, midlife women with hot flashes slept less than the recommended amount and health consequences of disrupted and inadequate sleep are well known and of concern. [31][32][33] Future research should explore other approaches for improving sleep quality, such as cognitive behavioral therapy for insomnia, to address the important problem of sleep disturbance in women during the menopausal transition and postmenopause.…”
Section: Discussionmentioning
confidence: 99%
“…While moderate sleep disturbance leads to stress and homeostasic imbalance (Killick et al 2012;Pellegrino et al 2012;Moller-Levet et al 2013;Gonnissen et al 2013), controlled laboratory studies in rodents have shown that prolonged sleep deprivation causes serious physiological and immunological deficits, eventually causing death (Rechtschaffen et al 1983;Bergmann et al 1989a;Everson et al 1994).…”
Section: Introductionmentioning
confidence: 99%